Auctioning immigration visas - David R. Collie (Cardiff University, Cardiff Business School, 2007)
Freeman (2006) suggested that auctioning immigration visas and redistributing the revenue to native residents in the host country would increase migration from low-income to high-income countries. The effect of the auctioning of immigration visas, in the Ricardian model from Findlay (1982), on the optimal level of immigration for the host country is considered. It is shown that auctioning immigration visas will lead to a positive level of immigration only if the initial wage difference between the host country and the source country is substantial. The cost of the immigration visa is more than half the earnings of the immigrant worker.
Keywords: 330; Einwanderung; Internationale Arbeitsmobilität; Reisebestimmungen; Auktion; Lohnniveau; Außenwirtschaftstheorie; Theorie